$δ$-Almost Ricci soliton on 3-dimensional trans-Sasakian manifold - Acet, T. (Carpathian Mathematical Publications, 2024)
In this paper, we consider $δ$-almost Ricci soliton on 3-dimensional trans-Sasakian manifold admitting $η$-parallel Ricci tensor. We give some conditions for $P· φ =0$, $P· S=0$, $Q· P=0$. Also, we show that there is almost pseudo symmetric $δ$-almost Ricci soliton on 3-dimensional trans-Sasakian manifold admitting cyclic Ricci tensor. Finally, we give an example for verifying the obtained results.